The Relationship between Quality of Life and Perception Over Social Reintegration in Patients Suffering from Aphasia: the Mediating Role of Social Support and Moderator Role of Gender and Family Support - Camelia Daniela ODAGIU (CUCU); Andreea Raluca ADAM; Florinda Tinela GOLU (Modern Medicine)
Background. The quality of life in patients suffering from aphasia, survivors of a stroke, is considerably lower compared to patients who have suffered from other types of stroke. In order to observe the changes that occur at a psychological level in patients suffering from aphasia, it is necessary to investigate the relationship between quality of life and their social reintegration. Objectives. This cross-sectional research aims to identify those elements of quality of life that can enhance a healthy and stable social reintegration over time in patients suffering from aphasia. Materials and methods. The research was performed on a sample of 103 patients suffering from aphasia. Participants answered four questionnaires: Stroke and Aphasia Quality of Life Scale-39 (SAQOL-39), The Community Integration Questionnaire Revisited (CIQ), Perceived Social Support Questionnaire (F-SozU) and Perceived Social Support - Family Form (PSS- Fa). The data were processed via SPSS V28 and Process V3.5. Results. The quality of life is a statistically significant predictor for the social reintegration of patients suffering from aphasia. Gender and family support were not found to be significant moderators of the relationship between quality of life and social reintegration. Social support was found to be a statistically insignificant mediator in the relationship between quality of life and social reintegration of patients suffering from aphasia.